OBSERVATIONS ON THE PRIMARY MARINE PRODUCTIVITY OF NORTHWESTERN INDONESIAN WATERS - Dotty, Maxwell S.; Soeriaatmadja, Raden Engkoes; Soegiarto, Aprilany (Marine Research in Indonesia, 1963)
During the fall months of 1957, a scientific cruise was completed in some of the more northwestern fishery areas of Western Indonesia (Fig. 1) on the Indonesian research vessel "Samudera". One of the principal objectives of this cruise was to determine the rates at which inorganic carbon is converted to organic material relative to the waters of the Pacific further east. The physical nature of the waters and the hydrographic results of related cruises have been reported (e.g., SOERIAATMADJA, 1956a & b; SJARIF, 1959; WYRTKI, 1961) elsewhere.